The Influence of Student Management on Students' Learning Achievement at State 1 Junior High School Tondano, Minahasa District - Rawis, Joulanda A M; Tambingon, Henny Nikolin; Lengkong , Jeffry Sony Junus; Qowi, Moh.; Tendean, Sherly D; Manumpil, Yulit B.; Namsa, Yohanis (International Journal of Information Technology and Education, 2024)
This study is motivated by studies introduction which shows para educator / Teacher in SMP Negeri 1 Tondano was not involved in the selection. However, they are still educators/teachers this is involved in management in field studentship, based on the results of interviews with the head school. So, researchers offer the involvement of students and teachers in educational management. This research aims to find out how student management is implemented at SMP Negeri 1 Tondano. This research method is quantitative research, meaning research that focuses on or produces numbers ( descriptive data) with a sample of 37 people. The results of this research show that the results of inferential statistical analysis regarding the influence of student management on student learning achievement at SMP Negeri 1 Tondano show that the results of a simple regression test show the influence of student management as seen from the results of the assessment of 37 respondents on student learning achievement which has T = - 1.211 with a significance value of 0.234 > 0.05, which means that H 0 is accepted and H 1 is rejected or there is no influence of student management on student learning achievement at SMP Negeri 1 Tondano.